Whole-Genome Characteristics and Polymorphic Analysis of Vietnamese Rice Landraces as a Comprehensive Information Resource for Marker-Assisted Selection - Hien Trinh (International Journal of Genomics, 2017)
Next generation sequencing technologies have provided numerous opportunities for application in the study of whole plant genomes. In this study, we present the sequencing and bioinformatic analyses of five typical rice landraces including three indica and two japonica with potential blast resistance. A total of 688.4 million 100 bp paired-end reads have yielded approximately 30-fold coverage to compare with the Nipponbare reference genome. Among them, a small number of reads were mapped to both chromosomes and organellar genomes. Over two million and eight hundred thousand single nucleotide polymorphisms (SNPs) and insertions and deletions (InDels) in indica and japonica lines have been determined, which potentially have significant impacts on multiple transcripts of genes. SNP deserts, contiguous SNP-low regions, were found on chromosomes 1, 4, and 5 of all genomes of rice examined. Based on the distribution of SNPs per 100 kilobase pairs, the phylogenetic relationships among the landraces have been constructed. This is the first step towards revealing several salient features of rice genomes in Vietnam and providing significant information resources to further marker-assisted selection (MAS) in rice breeding programs.